Injectable Shear-Thinning Hydrogels for Minimally Invasive Delivery to Infarcted Myocardium to Limit Left Ventricular Remodeling. (October 2016) - Rodell, Christopher B.; Lee, Madonna E.; Wang, Hua; Takebayashi, Satoshi; Takayama, Tetsushi; Kawamura, Tomonori; Arkles, Jeffrey S.; Dusaj, Neville N.; Dorsey, Shauna M.; Witschey, Walter R.T.; Pilla, James J.; Gorman, Joseph H.; et al.
Abstract : Background—: Injectable, acellular biomaterials hold promise to limit left ventricular remodeling and heart failure precipitated by infarction through bulking or stiffening the infarct region. A material with tunable properties (eg, mechanics, degradation) that can be delivered percutaneously has not yet been demonstrated. Catheter-deliverable soft hydrogels with in vivo stiffening to enhance therapeutic efficacy achieve these requirements. Methods and Results—: We developed a hyaluronic acid hydrogel that uses a tandem crosslinking approach, where the first crosslinking (guest–host) enabled injection and localized retention of a soft (<1 kPa) hydrogel. A second crosslinking reaction (dual-crosslinking) stiffened the hydrogel (41.4±4.3 kPa) after injection. Posterolateral infarcts were investigated in an ovine model (n≥6 per group), with injection of saline (myocardial infarction control), guest–host hydrogels, or dual-crosslinking hydrogels. Computational (day 1), histological (1 day, 8 weeks), morphological, and functional (0, 2, and 8 weeks) outcomes were evaluated. Finite-element modeling projected myofiber stress reduction (>50%; P <0.001) with dual-crosslinking but not guest–host injection. Remodeling, assessed by infarct thickness and left ventricular volume, was mitigated by hydrogel treatment. Ejection fraction was improved, relative to myocardial infarction at 8 weeks, with dual-crosslinking (37% improvement; P =0.014) and guest–host (15% improvement; P =0.058) treatments. Percutaneous delivery via endocardial injection was investigated with fluoroscopic and echocardiographic guidance, with delivery visualized by magnetic resonance imaging. Conclusions—: A percutaneous delivered hydrogel system was developed, and hydrogels with increased stiffness were found to be most effective in ameliorating left ventricular remodeling and preserving function. Ultimately, engineered systems such as these have the potential to provide effective clinical options to limit remodeling in patients after infarction. Abstract : Supplemental Digital Content is available in the text.